2021
DOI: 10.1007/s41109-021-00407-1
|View full text |Cite
|
Sign up to set email alerts
|

The network of international trade in services

Abstract: While the share of services in international trade has been increasing very slowly over the years, oscillating around 20 per cent since the 1990s, their role has constantly gained importance. Trade in services certainly faces many more obstacles than trade in goods, but its impact on globalization and countries’ competitiveness is crucial, and it is therefore worth investigating its characteristics. The present work aims to analyse the networks of international trade in services and to unveil specific properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other researchers have also used "product mapping" (Ambroziak & Stefaniak, 2022;Widodo, 2009); however, this study uses correspondence analysis to visualise the profile of services across the countries' profiles. As in Tajoli, Airoldi, and Piccardi (Tajoli et al, 2021), the study revealed that mapping the profiles of products and countries identifies the trade patterns much more clearly than the sole volume of traded services.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other researchers have also used "product mapping" (Ambroziak & Stefaniak, 2022;Widodo, 2009); however, this study uses correspondence analysis to visualise the profile of services across the countries' profiles. As in Tajoli, Airoldi, and Piccardi (Tajoli et al, 2021), the study revealed that mapping the profiles of products and countries identifies the trade patterns much more clearly than the sole volume of traded services.…”
Section: Introductionmentioning
confidence: 90%
“…Firm-level studies began appearing in the 1990s (Bernard & Jensen, 1999;Bernard & Wagner, 1997;Melitz, 2003), with more recent studies published on service trading firms (Ambroziak & Stefaniak, 2022;Ariu, 2016;Hornok & Koren, 2017;Tajoli et al, 2021;Temouri et al, 2013;Wagner, 2021;Yi et al, 2022). However, there has not been enough research on service trading firms (Benkovskis et al, 2019;Hornok & Koren, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…What is more, Figure 2 shows that the network density of financial services is growing gradually by years, from less than 0.7 to more than 0.8 [10]. This is an index that can indicate the degree of interaction of groups' member.…”
Section: Analysis On the Problemsmentioning
confidence: 95%
“…Core regions contribute significantly to the world's total exports and imports, boasting diverse economies, advanced infrastructure, and skilled labor. Figure 3 illustrates the distribution of global trade volume across core, semi-peripheral, and peripheral regions [10].…”
Section: Analysis On the Problemsmentioning
confidence: 99%
“…While most countries are connected in service trade, a small group of countries dominates the majority of flows. The central positions in service networks are predominantly occupied by advanced countries while emerging and developing nations rarely display high centrality [1]. Sajedianfard et al addressed the common issue of missing data in trade network analysis, where some countries do not report tra de flows.…”
Section: Related Researchmentioning
confidence: 99%